1972
DOI: 10.2355/isijinternational1966.12.102
|View full text |Cite
|
Sign up to set email alerts
|

Macrostructure of and Segregation in Continuously Cast Carbon Steel Billets

Abstract: The macro., tructure 0/ and the segregation in contin1/ollsly cast carbon steel billets with 80 to 250 mill square and 2()0 x 370 mm sectioll u-ere il1l'estigated. The results were summarized as follows. (1) The length ~f columnar clystal and the thickness of cen tral segre-.I!,ated :::one are increased, and the celltral porosit), and segregation become worse, with increase of costing sU/Jerheat temperature. (2) The absolute thickness of central segregated :::one is increased with increase of the section oj sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…5-8 reveals only a columnar crystal zone for all the heat samples. Figure 5 shows first group sample (heat 2), with large single 'V' segregates with discontinuous mini-ingotism 31 and discontinuous filled interdendritic cracks in the upper and bottom areas. The distance between 'V' segregates changes from 12 to 15 mm as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5-8 reveals only a columnar crystal zone for all the heat samples. Figure 5 shows first group sample (heat 2), with large single 'V' segregates with discontinuous mini-ingotism 31 and discontinuous filled interdendritic cracks in the upper and bottom areas. The distance between 'V' segregates changes from 12 to 15 mm as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This agrees well with the measurements and predications of bulging level by Miyazawa and Schwerdtfeger, 60 where they concluded that the major cause of centreline macrosegregation is solid shell bulging. In addition to the bulging shape, several operational factors have been reported to increase the severity of centreline segregation such as steel composition, 61 structure crystal, 62 casting speed, 63 tundish superheat, 64 section size, 65 EMS 45 and, finally, the characteristics of mechanical soft reduction technique. 18 These factors affect the central quality of steel slabs by different segregation levels.…”
Section: Centreline Zonementioning
confidence: 99%
“…Wyższymi współczynnikami wzbogacenia w pierwiastki stopowe i domieszkowe niż segregacja międzydendrytyczna, charakteryzuje się makrosegregacja [41]. Makrosegregacja środkowa i nieosiowe segregacje o wielkości pośredniej, do których należy segregacja typu "V", wykazują istotną różnicą w stosunku do segregacji międzydendrytycznej, którą jest wzbogacenie w węgiel strefy makrosegregacji [70][71][72]. Segregacja węgla nie występuje (lub występuje w bardzo niewielkim stopniu) w obszarach międzydendrytycznych, ze względu na wyrównywanie się stężenia węgla pomiędzy obszarami ramion dendrytów i przestrzeni międzydendrytycznych.…”
Section: Ewolucja Struktury Wlewków Ciągłych Ze Stali Niestopowych I Niskostopowych W Trakcie Przeróbki Plastycznej Na Gorącounclassified